1988
DOI: 10.1212/wnl.38.8.1207
|View full text |Cite
|
Sign up to set email alerts
|

Hemispatial neglect affected by non‐neglected stimuli

Abstract: Patients with hemispatial neglect fail to cancel lines distributed on one side of a piece of paper. This defect is thought to be induced by a deficit in the neuronal systems that mediate attention, intention, and exploration toward and in the hemispace contralateral to the lesion. However, an alternate (but not mutually exclusive) interpretation is that the patients are either strongly attracted to or impaired in disengaging from the stimuli occupying the other, non-neglected hemispace. We tested ten patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(120 citation statements)
references
References 3 publications
9
105
1
Order By: Relevance
“…It has been repeatedly demonstrated that patients do not simply neglect left objects, but are attracted by right ones. In an ingenious variant of the line cancellation task, Mark et al [86] had 10 patients with left neglect erase lines or draw over them with a pencil mark, and found lesser neglect in the`erase' than in the`draw' condition. Mark et al concluded that right-sided lines attracted patients' attention when they were crossed by a pencil mark, whereas rendering these lines invisible by erasing them obviously nulli®ed this effect, thus decreasing neglect.…”
Section: A Rightward Attentional Bias In Left Neglectmentioning
confidence: 99%
“…It has been repeatedly demonstrated that patients do not simply neglect left objects, but are attracted by right ones. In an ingenious variant of the line cancellation task, Mark et al [86] had 10 patients with left neglect erase lines or draw over them with a pencil mark, and found lesser neglect in the`erase' than in the`draw' condition. Mark et al concluded that right-sided lines attracted patients' attention when they were crossed by a pencil mark, whereas rendering these lines invisible by erasing them obviously nulli®ed this effect, thus decreasing neglect.…”
Section: A Rightward Attentional Bias In Left Neglectmentioning
confidence: 99%
“…However, the location of omissions can change as a function of starting position (Robertson & North, 1993) and search strategy (Chatterjee et al, 1992b). The number of omissions can change as a function of demands on selective attention (Rapcsak et al, 1989), the presence and location of distracting stimuli (Kaplan et al, 1991), and the method of cancellation (Ishiai et al, 1990;Mark et al, 1988;Robertson & North, 1993). In addition, Chatterjee et al (1992a,b,c) demonstrated a stimulus-response relationship on cancellation tests in neglect such that a greater proportion of target stimuli are omitted as the total number of cancellation items increases.…”
Section: Introductionmentioning
confidence: 99%
“…Mark et al (1988) required neglect patients to draw on targets scattered on a sheet with a pencil mark or to erase them, found more left omission in the 'draw' than in the 'erase' condition, and concluded that right-sided (cancelled) targets continued to attract patients' attention, thereby increasing left neglect. In a Posner-type reaction time paradigm (see Posner, Walker, Friedrich, & Rafal, 1984), D'Erme, Robertson, Bartolomeo, Daniele, and Gainotti (1992) found slower responses to left-sided targets when targets occurred in one of two bilateral boxes than when they occurred without boxes, as if the right-sided box again attracted patient's attention.…”
Section: Discussionmentioning
confidence: 99%
“…Per contra, some attentional accounts of neglect (e.g. Gainotti et al, 1991;Kinsbourne, 1993) have stressed that right-sided items are likely to attract patients' attention; the more objects presented on the 'unaffected' side, the greater the neglect (Mark, Kooistra, & Heilman, 1988). In the present study, the aim was to explore the effect of the presence or absence of such competing stimuli on a task similar to that employed by Halligan and Marshall (1991), in the expectation that this additional experimental condition would help elucidate the effects of any attentional deficit.…”
Section: Introductionmentioning
confidence: 99%